Black Empowerment and Affirmative Action: The Incongrous Irony of South Africa’s Multiracial Democracy - Forti, Etienne Langmia (Advances in Social Sciences Research Journal, 2025)
The central focus of this paper is the racially engendered irony that underlying the African National Congress’(ANC) use of affirmative action as a policy to achieve social justice by empowering the black population. The discussion centres on fictionalized examples from Nicholas Mhlongo’s Dog Eat Dog and After Tears and highlights how the rise in racial tension observed in the country’s public sphere is a consequence of the policy’s seemingly racist and/or racial nature. The irony of affirmative action in post-apartheid South Africa can be examined from two broad, interconnected perspectives: the government’s initiatives inspired by affirmative action and the general black population’s response to the policy. The article argues that despite the ANC’s commendable intent in implementing affirmative action, some of the actions of the new leadership - driven by this policy – subtly reflects the very racial and/or racist tendencies it once fought against. Ultimately, the irony of South Africa’s affirmative action policy is shaped by its often racialised repercussions, which arise from a public that has not fully grasped the spirit of the policy and frequently misconstrues the government’s initiatives. The discussion in the paper is shaped by new historicists’ and postcolonial theoretical considerations as it borrows from the major concepts of New Historicism such as those propounded by Anton Kaes, Louis Montrose, Jerome McGann, and the Postcolonial concepts of Centre/Margin, Self/Other binaries, Race, Class and Ethnicity.